2014
DOI: 10.1080/10615806.2014.910596
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting adolescent posttraumatic stress in the aftermath of war: Differential effects of coping strategies across trauma reminder, loss reminder, and family conflict domains

Abstract: These findings shed light on ways in which trauma reminders, loss reminders, and family conflict may intersect with coping responses to influence adolescent postwar adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 33 publications
4
20
1
Order By: Relevance
“…A more frequent use of engagement coping strategies in everyday situations, such as problem-focused coping and cognitive restructuring, was associated with higher levels of PTSD symptoms and internalizing problems, which is inconsistent with studies that found engagement strategies to be related to lower levels of mental health problems in refugee children and adults [13,14,[70][71][72]. However, other studies found that more problem-focused coping was associated with higher levels of internalizing problems in sample of adult Syrian refugees living in Turkey close to the Syrian border [73] and with the presence of PTSD in Bosnian refugee youth waiting for the resolution of their asylum claims [15].…”
Section: Ucla-ri-5contrasting
confidence: 80%
See 1 more Smart Citation
“…A more frequent use of engagement coping strategies in everyday situations, such as problem-focused coping and cognitive restructuring, was associated with higher levels of PTSD symptoms and internalizing problems, which is inconsistent with studies that found engagement strategies to be related to lower levels of mental health problems in refugee children and adults [13,14,[70][71][72]. However, other studies found that more problem-focused coping was associated with higher levels of internalizing problems in sample of adult Syrian refugees living in Turkey close to the Syrian border [73] and with the presence of PTSD in Bosnian refugee youth waiting for the resolution of their asylum claims [15].…”
Section: Ucla-ri-5contrasting
confidence: 80%
“…In the coping literature, engagement coping strategies, including problemfocused coping, support seeking, emotion regulation and cognitive restructuring, have been generally associated with positive mental health outcomes [12]. In a study with waraffected Bosnian adolescents [13], a greater use of engagement strategies was associated with lower levels of PTSD symptoms. Syrian children who coped by acquiring social support and trying to reframe events also reported fewer PTSD symptoms [14].…”
Section: Introductionmentioning
confidence: 99%
“…The grief field is in need of research designs and conceptual frameworks that clarify potentially differential relations between specific characteristics of bereavement (e.g., circumstances of the death [13]), age-related reactions to the loss (e.g., coping [14], grief reactions [15]), and developmental trajectories across the lifespan (10,16,17), including risks for proximal and distal adverse outcomes (e.g., substance abuse, depression) (5). The Keyes et al study contributes to such theory-building work by using a large population-based sample and focusing on a range of psychiatric outcomes across the life course.…”
Section: In Search Of Mediating Causal Pathwaysmentioning
confidence: 99%
“…The individual. Research on risk and protective factors, and specifically research with refugee children, has identified several psychological factors, such as self-regulation and coping skills, that are associated with better mental health (Aitcheson et al, 2017;Howell et al, 2015). Cognitive resources may protect individuals or promote adaptive development by enabling them to cope with environmental stressors.…”
Section: Facet 1: the Multisystemic Nature Of Psychological Resiliencementioning
confidence: 99%